2016
DOI: 10.1016/j.coastaleng.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of wave overtopping at vertical structures

Abstract: Prediction of wave overtopping rate is an important step in the functional design of vertical coastal structures. In this study, scaling arguments and data mining approaches were used to derive formulae for the prediction of wave overtopping rate at vertical and nearly vertical structures. An extensive database mainly selected from the CLASH including impulsive and non-impulsive, low and high freeboard and composite structures were used for formula development. The obtained dimensionless overtopping rates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…Backshores historically unimpacted by incident wave overtopping, may become vulnerable with higher sea levels, and Arns et al [116] suggested that future water levels will amplify wave runup design heights by ∼50% in currently impacted areas. Although wave overtopping has received sustained attention in the literature (e.g., [117][118][119][120]), wave runup and overtopping are considered significant deficiencies in current modeling methodologies [28,121,122], and have been recognized as a key future research area [123].…”
Section: Wave Overtoppingmentioning
confidence: 99%
“…Backshores historically unimpacted by incident wave overtopping, may become vulnerable with higher sea levels, and Arns et al [116] suggested that future water levels will amplify wave runup design heights by ∼50% in currently impacted areas. Although wave overtopping has received sustained attention in the literature (e.g., [117][118][119][120]), wave runup and overtopping are considered significant deficiencies in current modeling methodologies [28,121,122], and have been recognized as a key future research area [123].…”
Section: Wave Overtoppingmentioning
confidence: 99%
“…R.avaflow, a two-phase model that was developed to simulate debris flows into fluid bodies (Pudasaini, 2012), has been applied to simulate debris flows such as those that would be present in a GLOF (Mergili et al, 2017). Few researchers have looked at the issue of wave run-up (e.g., Synolakis, 1987Synolakis, , 1991Muller, 1995;Liu et al, 2005;Capel, 2015;Romano et al, 2015;Etemad-Shahidi et al, 2016), and most use empirical formulas or simplified approaches for wave run-up calculations, making assumptions about the lake geometry that may not be realistic (e.g., uniform water depth and a regularly sloped dam).…”
Section: Impulse Waves Generated From Avalanches and Landslidesmentioning
confidence: 99%
“…The density of the avalanche material that is typical for this type of GLOF, a mixture of snow, rock, and ice, is nearly the density of water (Schneider et al, 2014); therefore, water was used in place of the avalanche fluid, and the volume of the water that represents the avalanche was the same as the total avalanche volume. This is the same approach used by Worni et al (2014) and Fah (2005). The two fluids (water and the avalanche material) have different viscosities, but the model was adjusted to account for the effects of the lower viscosity of water (less dissipation of energy as it flows towards the lake).…”
Section: Avalanche Sourcementioning
confidence: 99%
“…However, these studies still focus on simple cases and geometries rather than real-world scenarios. Few researchers have looked at the issue of wave run-up (e.g., Synolakis, 1987 and1991;Muller, 1995;Liu et al, 2005;Capel, 2015;Romano et al, 2015;Etemad-Shahidi et al, 2016), and most use empirical formulas or simplified approaches for wave run-up calculations, making assumptions about the lake geometry that may not be realistic (e.g., uniform water depth and a regularly sloped dam). 15…”
Section: Impulse Waves Generated From Avalanches and Landslidesmentioning
confidence: 99%